Implementasi Teknologi Internet of Things Pada Sistem Pemantauan Kebocoran Gas LPG dan Kebakaran Menggunakan Database Pada Google Firebase - Abi Sabila Mustaqim; Danny Kurnianto; Fikra Titan Syifa (Teknik Elektro Politeknik Negeri Padang, 2020)
Fire due to Liquefied Petroleum Gas (LPG) gas leak is one of the disasters that still often occurs in the community. Community ignorance of safety standards in using LPG gas is one reason. Fires can be prevented if at the time of the LPG gas leak can be detected earlier. Therefore we need a system that can monitor the condition of gas leaks and fires remotely. Internet of things (IoT) technology can be applied to this monitoring system so that information on LPG gas leaks and fires can be monitored remotely. The Internet of Things (IoT) based LPG and Fire leak monitoring system is a concept that utilizes internet connectivity between smartphone devices connected to sensor devices. The devices used to support this system include NodeMCU ESP8266 as a microcontroller and as a liaison to the internet, MQ-6 gas sensors and flame sensors as sensors for detecting gas and fire leaks, buzzers as alarms, and fans as neutralizing gas levels in the room. Data obtained by the sensor will be uploaded to the database via the internet and can be accessed through an android application. The results of the design show that the android application can display notifications when a gas leak or fire occurs. In testing the performance of data transmission, the results show that the highest data transmission delay is 64,61 seconds, and the lowest delay time is 61,56 seconds, the highest throughput value is 747,6 bits/second, and the lowest value is 285,4 bits/second.